Konseling Fitri: Model Konseling Berbasis Juz Qurani - Lutfi Fauzan (Indonesian Journal of Educational Counseling, 2018)
FITRI COUNSELING: JUZ QURANIC-BASED ON COUNSELING MODEL. Al-Qur’an as holly book that has scientific content can be revealed about human being with all their potencies and their differencies individual characters. The revealing scientific treasure is approached by Bayani method, Irfani, Burhani and HAQ mehod. The result shows that human has five natural (fitri) potencies, and has individual differencies, they are 30 personality types as like as quantity of Al-Qur'an juz. Developing human personality should be applied based on the character difference. Therefore, the juz qurani-based on idea and counseling model was made. The counseling model has five main stage and some specific behavior change techniques.